Postulates of the Power and Educational Training in Colombia - Casas, Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper analyzes the relationship between the postulates of the power and Colombian education, particularly the correspondence between labor training and the reproduction of the established ideological order. The type of research is the critical ana - lyzes of the discourse, through a dialogical method among power theories of Foucault (1988, 2002) and Althusser (1969, 1971, 1988). Oppositions of these two theories about power arise because they have been thought within the institutional frameworks, such as schools (Foucault, 2002) and the unavoidable relationship with political ideologies and policies (Althusser, 1988). Disparities and confrontations among these two theories on power are shown. The conclusion shows the power relations be- tween the Colombian State and the public school scenarios, as well as the way in which power devices work in these scenarios (Jäger, 2003), always from the possibility of human emancipation to transform its environment.